Animal disease research for food security in sub-Saharan Africa: The case of theileriosis and trypanosomiasis in the Preferential Trade Area - Mukhebi, A.W.; Perry, Brian D.; Kruska, Russell L. (United States Agency for International Development, 1996)
This paper highlights the growing divergence between the supply and demand for livestock products in sub-Saharan Africa with special reference to the Preferential Trade Area (PTA) region. Livestock diseases, especially theileriosis and trypanosomiasis, among other constraints, are identified as a major contributor to the growing deficits in livestock products. The impacts of these two diseases and of their control is discussed, and the role of the International Laboratory for Research on Animal Diseases in developing improved disease control measures is highlighted.